2016
DOI: 10.1002/dev.21424
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal eyelid conditioning during sleep

Abstract: Using an eyelid conditioning paradigm modeled after that developed by Little, Lipsitt, and Rovee-Collier (1984), Fifer et al. (2010) demonstrated that newborn infants learn during sleep. This study examined the role of sleep state in neonatal learning. We recorded electroencephalogram (EEG), respiratory, and cardiovascular activity from sleeping full term newborn infants during delay eyelid conditioning. In the experimental group (n = 21), a tone was paired with an air puff to the eye. Consistent with Fifer et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In detail, it has been reported that sleeping newborns are able to distinguish between various auditory stimuli, as demonstrated for speech vs. music [ 15 ], standard vs. deviant vowels [ 16 , 17 ], and forward vs. backward voices [ 18 ]. Furthermore, sleeping infants are reported to detect prosodic speech cues [ 19 ], discriminate anger and fear in voices [ 20 ], and even learn during sleep, as evidenced by increased eye movement responses to a tone earlier paired with an air puff [ 21 , 22 ]. Also, sleeping newborns (aged two days to six weeks) are reported to show heartrate de- or accelerations to various auditory stimuli [ 11 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In detail, it has been reported that sleeping newborns are able to distinguish between various auditory stimuli, as demonstrated for speech vs. music [ 15 ], standard vs. deviant vowels [ 16 , 17 ], and forward vs. backward voices [ 18 ]. Furthermore, sleeping infants are reported to detect prosodic speech cues [ 19 ], discriminate anger and fear in voices [ 20 ], and even learn during sleep, as evidenced by increased eye movement responses to a tone earlier paired with an air puff [ 21 , 22 ]. Also, sleeping newborns (aged two days to six weeks) are reported to show heartrate de- or accelerations to various auditory stimuli [ 11 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…These effects appear to be further modulated by sleep state, with more significant learning seemingly occurring during deeper sleep stages ( Tarullo et al. 2011 , 2016 ). It would be of great interest in future studies to understand how it may have contributed to our results.…”
Section: Discussionmentioning
confidence: 99%
“…EBC does not require active participation of the subject. In our paradigm, the patient was watching a silent movie during the experiment; in newborns, EBC can even be performed during sleep (30,31). Thus, the outcome of EBC are unlikely to be related to motivational deficits in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%